Peter C. Petersen letter to Nicholas S. Halmi regarding winter bird sightings, February 10, 1979 - Petersen, Peter C.et al (1979)
Letter from Peter C. Petersen to Nicholas S. Halmi regarding winter bird sightings in the Quad Cities area, February 10, 1979. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1978-1979. Epson - sheet feed/flatbed